2020
DOI: 10.1532/hsf.2921
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Coronary Artery Compromise Post Non-Coronary Cardiac Surgery in Patients With Normal Coronaries

Abstract: Background: Unexpected events in cardiac surgery may increase morbidity and mortality. We present rare complications related to coronary arteries in non-coronary cardiac surgery in adults and pediatrics. Patients and Methods: We retrospectively reviewed our surgical left-sided valve procedures and aortic root reconstruction for patients with documented coronary ostial injury or left circumflex artery (LCX) between January 2012 and December 2019. Preoperative echocardiography was the standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…We would like to thank Professor Al‐Ebrahim 1 for his letter regarding our case report of an acute coronary occlusion after surgical replacement of the aortic valve 2 . We read with interest their previous series of iatrogenic coronary artery compromise post cardiac surgery 3 . The authors advocate a prompt diagnosis and percutaneous treatment of this type of complication.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…We would like to thank Professor Al‐Ebrahim 1 for his letter regarding our case report of an acute coronary occlusion after surgical replacement of the aortic valve 2 . We read with interest their previous series of iatrogenic coronary artery compromise post cardiac surgery 3 . The authors advocate a prompt diagnosis and percutaneous treatment of this type of complication.…”
mentioning
confidence: 96%
“…2 We read with interest their previous series of iatrogenic coronary artery compromise post cardiac surgery. 3 The authors advocate a prompt diagnosis and percutaneous treatment of this type of complication. In our case, we obtained a clear and prompt diagnosis of postoperative ischemia immediately after coming off cardiopulmonary bypass with obvious ECG changes and transoesophageal echocardiographic findings of hypokinesia.…”
mentioning
confidence: 99%
“…To the Editor, We read with interest the case report by Ackah et al 1 We previously reported, in a cohort study, 2…”
mentioning
confidence: 97%